Zaman baru Islam Indonesia : pemikiran & aksi politik Abdurrahman Wahid, M. Amien Rais, Nurcholish Madjid, Jalaluddin Rakhmat - Malik, Dedy Djamaluddin, 1958-; Ibrahim, Idi Subandy, 1969- (Bandung : Zaman Wacana Mulia, 1998)
Political Islamic thoughts of four prominent Indonesian Muslim intellectuals; political conditions in Indonesia, Islam and state; analysis.
Originally presented as the author's thesis (magister sains--Universitas Padjadjaran, 1992): Under title: Pemikiran cendekiawan Muslim, 1985-1990.
Includes bibliographical references (p. 308-323) and index.
Keywords: Islam -- Indonesia; Islam and state -- Indonesia; Scholars, Muslim -- Indonesia; Indonesia -- Politics and government -- 1966-